Incorporating date palm fibers for sustainable friction composites in vehicle brakes - Zeina Mahmoud Alian Ali Ammar; Mahmoud A. Adly; Sherif Mehanny (2024)
This study explores the incorporation of date palm fibers into friction composites for eco-friendly brake pads, examining the influence of matrix composition, reinforcement material, and abrasive filler on mechanical and tribological properties. Epoxy binder content initially boosts compressive strength and hardness, peaking at 25% weight percentage, while wear rate fluctuates. Palm Frond Midrib (PFM) enhances mechanical properties, with compressive strength peaking at 30% PFM. Calcium carbonate (CaCO3) filler shows complex effects on compressive strength and hardness. Overall, PFM demonstrates promise as a sustainable alternative to traditional palm kernel fibers, with optimized formulations showing superior mechanical properties compared to commercial pads. Wear rate and COF are affected by epoxy content and CaCO3 filler concentration, underscoring the need for parameter optimization. This research contributes to advancing eco-friendly automotive materials, emphasizing the importance of utilizing natural resources to mitigate environmental and health risks associated with conventional brake pad materials.
(3JSJcTa gPg GdOQGSI EOeGL CdjGa fNjd GdJeQ aj eQcHGJ GdGMJcGc ddhSGFO GdaQGed GdUOjbI ddHjFI, MjK JaMU JCKjQ JQcjH GdeUahaI heGOI GdJYRjR hGdedA GdcGTW Ydi GdNUGFU GdejcGfjcjI hGdJMdjdjI(B. (3jDOj eMJhi eGOI GdQHW (B((3GdEjHhcSj(B) (3Edi RjGOI GdbhI GdVGZWI hGdUdGOI aj GdHOGjI, MjK jJMbb GdPQhI YfO fSHI hRf (B25(3%, aj Mjf jJPHPH eYOd GdJBcd(B. (3jYRR JYRjR CdjGa GdfNjd GdejcGfjcjI, MjK JJMbb GdPQhI aj bhI GdVZW YfO (B30(3% ef fSHI GdCdjGa(B. (3JXgQ eGOI GdedA (B((3cQHhfGJ GdcGdSjhe(B) (3JCKjQGJ eYbOI Ydi bhI GdVZW hGdUdGOI(B. (3HUaI YGeI, JXgQ CdjGa GdfNjd oeMJekdG cHOjd eSJOGe dCdjGa fhGI GdfNjd GdJbdjOjI, MjK oJXgQ GdJQcjHGJ GdoeMqSfI GdNUGFU GdejcGfjcjI GdCaVd HGdebGQfI eY GdhSGFO GdJLGQjI(B. (3jJCKQ eYOd GdJBcd heYGed GdGMJcGc HeMJhi GdEjHhcSj hJQcjR edA cQHhfGJ GdcGdSjhe, eeG jDcO Ydi VQhQI JMSjf GdeYdeGJ(B. (3JSge gPg GdHMhK aj JbOe ehGO GdSjGQGJ GdUOjbI ddHjFI, MjK oJTOO Ydi CgejI GSJNOGe GdehGQO GdWHjYjI ddMO ef GdeNGWQ GdHjFjI hGdUMjI GdeQJHWI HehGO GdhSGFO GdaQGed GdJbdjOjI(B.s
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 69-74.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Mechanical Engineering; Brake Pads -- Natural Fiber -- Palm date -- Eco-Friendliness material